2011
DOI: 10.1111/j.1365-2966.2011.19958.x
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the relationship between Lyα and UV-selected galaxies: do theorists and observers ‘select’ the same objects?

Abstract: Lyman α emitters (LAEs) are galaxies that have been selected on the basis of a strong Lyα emission line in their spectra. Observational campaigns over the last decade have dramatically increased the sample of known LAEs, which now extends out to z= 7. These discoveries have motivated numerous theoretical studies on the subject, which usually define LAEs in their models based on sharp Lyα luminosity and equivalent width (EW) cuts. While broadly representative, this procedure does not mimic the selection from ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 100 publications
9
77
1
Order By: Relevance
“…Dijkstra & Wyithe 2012). However, at z > 6 the Lyα fraction decreases (Fontana et al 2010;Stark, Ellis, & Ouchi 2011;Pentericci et al 2011;Schenker et al 2012;Ono et al 2012;Caruana et al 2012Caruana et al , 2013Finkelstein et al 2013;Pentericci et al 2014;Schenker et al 2014;Tilvi et al 2014), in line with observations of the Lyα and UV luminosity functions of LAEs (again quantitatively consistent, see Dijkstra et al 2014).…”
Section: The Datasupporting
confidence: 70%
“…Dijkstra & Wyithe 2012). However, at z > 6 the Lyα fraction decreases (Fontana et al 2010;Stark, Ellis, & Ouchi 2011;Pentericci et al 2011;Schenker et al 2012;Ono et al 2012;Caruana et al 2012Caruana et al , 2013Finkelstein et al 2013;Pentericci et al 2014;Schenker et al 2014;Tilvi et al 2014), in line with observations of the Lyα and UV luminosity functions of LAEs (again quantitatively consistent, see Dijkstra et al 2014).…”
Section: The Datasupporting
confidence: 70%
“…While the exact relation between LAEs and LBGs remains a matter of debate, especially at z 6 (Verhamme et al 2008;Nagamine et al 2010;Dijkstra & Wyithe 2012), if the high-z LBG population being observed is indeed as young and metal-poor as LAEs, the method developed in this paper is equally applicable to the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, Verhamme et al (2008) propose that at a given redshift, LAEs and LBGs are the same population above a given limiting magnitude; for galaxies fainter than such magnitude, LAEs are less massive compared to LBGs. Finally, Dijkstra & Wyithe (2012) point out that observationally LAEs are chosen using sophisticated colour–colour selection techniques; they caution that simple cuts in EW and UV magnitude can lead to uncertainties in the simulated LAE number densities.…”
Section: Introductionmentioning
confidence: 99%